2018
DOI: 10.1016/j.micinf.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Cellular interactions of covR/S mutant group A Streptococci

Abstract: Group A Streptococci (GAS) are responsible for a wide array of non-invasive and invasive diseases and varying immune sequelae with high rates of mortality and morbidity. GAS strains with a mutation in their covR/S regulatory system are hypervirulent with an increased capacity for causing invasive disease. covR/S mutants augment their virulence through the up-regulation of important virulence factors and target host immune surveillance primarily by inhibiting neutrophils. An in-depth understanding of the immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Differential expression of GAS virulence factors is regulated by a multitude of transcriptional regulators, including the two‐component control of virulence regulatory system ( covRS ). In invasive GAS infections, spontaneous covRS mutations can cause an upregulation of several virulence factors, thereby promoting host‐adaptation and exacerbating disease (Langshaw, Pandey, & Good, 2018; Sumby, Whitney, Graviss, DeLeo, & Musser, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Differential expression of GAS virulence factors is regulated by a multitude of transcriptional regulators, including the two‐component control of virulence regulatory system ( covRS ). In invasive GAS infections, spontaneous covRS mutations can cause an upregulation of several virulence factors, thereby promoting host‐adaptation and exacerbating disease (Langshaw, Pandey, & Good, 2018; Sumby, Whitney, Graviss, DeLeo, & Musser, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…CovR/S mutants, a hypervirulent update of group A streptococci (GAS), target neutrophils, as reported by Langshaw et al Consequently, the authors underscore the soundness of developing multi-component vaccines, targeting separate virulence mechanisms in parallel [18].…”
Section: Times Of Technologymentioning
confidence: 80%
“…Further studies showed that the expression of HA and M protein components of S. pyogenes capsular layers led to inflammasome activation, blockage of neutrophil extracellular trap (NET) formation, and macrophage pyroptosis (Wessels 2019;Chang and Nizet 2020). (Hynes and Sloan 2016;Frick et al 2018;Kurosawa et al 2018;Langshaw et al 2018;Estafanos 2019;Zhang 2020).…”
Section: Accepted Articlementioning
confidence: 99%